Comparative Study on Dental Autograft & Bone Autogenous Graft for Socket Preservation - Seema Patil (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Autogenous bone grafts are regarded as the gold standard due to their osteoinductive, osteoconductive, and osteogenic qualities. Osteogenesis is the process by which graft cells that survive bone form new bone. Aim: To compare & determine the EF of DA with ABG for POSD after removal of mandibular 3rd Molar clinically & radiographically. Material & Method: 12 patiensy were inlcuded for the assessment of DA & ABG in 2 differents groups i.e. A & B. Result: We have found highy significant differnce MO, pain, swelling, BD and BH respectively. While non- significant difference was seen for BOP & COG for both the groups. Conclusion: When compared to the DA, there was a relatively smaller volume of ABG harvested, but it was sufficient to fill the socket up to the level of the CEJ. This resulted in a superior outcome after 6 months in terms of preserving the ridge BH, which was more pronounced on the side filled with DA.